A National Study on the Impact of Wildfire Smoke on Cause-Specific Hospitalizations Among Medicare Enrollees with Alzheimer’s Disease and Related Dementias from 2006 to 2016 - Do, Vivian; McBrien, Heather; Teigen, Katharine; Childs, Marissa L.; Kioumourtzoglou, Marianthi-Anna; Casey, Joan A. (Fire (Basel, Switzerland), 2025)
Older adults may experience worse wildfire fine particulate matter (PM2.5) smoke-related health effects due to conditions such as Alzheimer’s disease and related dementias (ADRDs). We evaluated whether wildfire PM2.5 was associated with acute hospitalizations among older adults with ADRD, linking modeled daily wildfire PM2.5 concentrations and circulatory, respiratory, anxiety, and depression hospitalizations from 2006 to 2016. We employed a case-crossover design and conditional logistic regression to estimate associations between lagged daily wildfire PM2.5 and hospitalizations. Also, we stratified cause-specific models by age, sex, emergency hospitalization status, and zip code-level urbanicity and poverty. The 1,546,753 hospitalizations among Medicare enrollees with ADRD were most coded for circulatory (71.7%), followed by respiratory (43.6%), depression (2.9%), and anxiety (0.7%) endpoints. We observed null associations between wildfire PM2.5 and circulatory, respiratory, and anxiety hospitalizations over the six days following exposure. Same-day wildfire PM2.5 was associated with decreased depression hospitalizations (rate ratio = 0.94, 95% CI: 0.90, 0.99). We saw some effect measure modifications by emergency hospitalization status and urbanicity. There were some stratum-specific effects for age, but the results remained mostly null. Future studies should use improved methods to identify ADRD and examine recent years with higher wildfire concentrations.